Utilização do óleo de andiroba (Carapa Guianensis) para a produção de sabão em combinação com extrato aquoso de cinzas - LIMA, Fabiane Silva de (2022)
Brazil stands out from other countries for having in its territory a vast collection of oilseed plants, which can be applied for various purposes. Andiroba oil (Carapa guianensis) is one of the species that stand out the most, because in addition to being used to treat some diseases, it has many other applications, among which the production of soaps is the focus of this study. study. Soap is the product resulting from the basic hydrolysis of animal or vegetable fats. Therefore, the present work aims to verify the quality of soap produced by hand from the alkaline hydrolysis applied to andiroba oil in combination with the aqueous extract of ash, in addition to determining, through physical-chemical analysis, some properties that guarantee the quality of the oil used. The results were significant, indicating that despite being a little explored application, andiroba oil has a relevant potential in the production of soaps.